2011
DOI: 10.1002/jbm.b.31803
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of electrical stimulation for improving periprosthetic attachment

Abstract: Transcutaneous osseointegrated implants (TOI) have been shown to improve functionality for patients with limb loss by allowing direct skeletal attachment between an exoprosthesis and host bone. However, a lengthy rehabilitation period has limited the expansion of TOI and may be accelerated with electrical stimulation. The purpose of this study was to determine the ability of direct current (DC) cathode stimulation to enhance osseointegration of intramedullary implants in skeletally matured rabbits. Bilateral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
3
27
0
1
Order By: Relevance
“…One of these mechanisms is the formation of electric potentials in load‐bearing bone upon application of mechanical stress (Rajabi, Jaffe, & Arinzeh, ; Riddle & Donahue, ). In vivo studies indicate that direct current electrical stimulation applied to an implant site enhances initial‐stage implant osseointegration, improves interfacial strength, and increases bone formation (Dergin et al, ; Isaacson et al, ; Salman & Park, ). In current clinical practice, electrical stimulation is used to treat non‐union fractures via direct current, inductive, and capacitive coupling procedures (Aleem et al, ; Griffin & Bayat, ; Kuzyk & Schemitsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of these mechanisms is the formation of electric potentials in load‐bearing bone upon application of mechanical stress (Rajabi, Jaffe, & Arinzeh, ; Riddle & Donahue, ). In vivo studies indicate that direct current electrical stimulation applied to an implant site enhances initial‐stage implant osseointegration, improves interfacial strength, and increases bone formation (Dergin et al, ; Isaacson et al, ; Salman & Park, ). In current clinical practice, electrical stimulation is used to treat non‐union fractures via direct current, inductive, and capacitive coupling procedures (Aleem et al, ; Griffin & Bayat, ; Kuzyk & Schemitsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…The first simulation is from an osseointegrated bone implant experiment, studying the effects of using direct current cathode stimulation to enhance the ability of implants to fuse into the skeletons of rabbits [26]. The second simulation is used for modeling the effects of EEG source on a human skull [17].…”
Section: Resultsmentioning
confidence: 99%
“…Electrically induced osseointegration has been demonstrated in humans [6, 7] and experimentally validated in an in vivo animal study [11] using the multiscale modeling process described herein as an initial measure. Preliminary work has demonstrated that electrical stimulation may alleviate problems with poor implant fit and fill [11] and with additional experimental refinement, may directly demonstrate the link between mutiscale modeling assumptions and periprosthetic skeletal attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary work has demonstrated that electrical stimulation may alleviate problems with poor implant fit and fill [11] and with additional experimental refinement, may directly demonstrate the link between mutiscale modeling assumptions and periprosthetic skeletal attachment. However, before electrical stimulation can be used as a therapeutic aid, model refinements which account for tissue orientation and fiber direction will be necessary to increase model accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation